Pill Esophagitis: Clinical and Endoscopic Profile - Pemmada, Vikas; Shetty, Athish; Murali, Megha; Shetty, Shiran; Musunuri, Balaji; Rajpurohit, Siddheesh; Bhat, Ganesh (Journal of Digestive Endoscopy, 2023)
Background Medications can rarely cause esophageal injury and present with acute symptoms. Multiple factors, including the type of medication, comorbidity, and method of ingestion play a role in causing drug-induced or pill esophagitis (PE). We analyzed the clinical, endoscopic, and histopathological profiles of PE cases at our gastroenterology outpatient clinic.Methods Medical records of PE cases were reviewed retrospectively over a period of 5 years at a tertiary care hospital in India from May 2017 to May 2022. The data were collected and analyzed using descriptive statistical analysis.Results A total of 30 patients diagnosed with PE were involved in the study. A slight male preponderance of 56.7% was noted with a mean age of 40.7 years. Odynophagia was the dominant symptom (70%) with a mean duration of symptoms of 5.63 days. The most common location was at the mid-esophagus (80%) followed by the lower esophagus (10%). The majority (56.7%; 17/30) had over-the-counter (OTC) drug consumption, followed by doxycycline (33.3%; 10/30). Kissing ulcers were seen in 30% of the subjects; 90% of the patients received a combination of proton pump inhibitors and sucralfate suspension for 2 weeks along with discontinuation of the causative drug, with a 96.7% resolution rate.Conclusion OTC medication and antibiotics such as doxycycline are the leading cause of PE. Prompt recognition and discontinuation of the causative drug are crucial in preventing complications. Patient education is vital in preventing PE regarding the usage of OTC medicines in developing countries.
Keywords: doxycycline; drug-induced esophagitis; drugs; over-the-counter; pill esophagitis; pill-induced esophagitis